Evidence for Pleistocene seed grinding at Lake Mungo, south‐eastern Australia. (April 2015) - Fullagar, Richard; Hayes, Elspeth; Stephenson, Birgitta; Field, Judith; Matheson, Carney; Stern, Nicola; Fitzsimmons, Kathryn
Abstract: Grinding stones and fragments have often been found in archaeological sites at Lake Mungo, south‐western New South Wales, and their function has mostly been inferred on the basis of grindstone morphology. Of particular interest has been the antiquity of grass seed grinding, which is usually associated with deeply grooved, large sandstone dishes. Previous studies of grinding stones from the region have found no compelling evidence for seed grinding prior to the Pleistocene/Holocene boundary. One of the problems has been that the grinding stones have been found on deflated surfaces and have been difficult to accurately provenance and date. Here, we report a functional study of 17 sandstone artefacts, recently collected from the central part of the Mungo lunette, where a suite of OSL ages have provided bracketing age estimates for the stratigraphic units. Ten artefacts are attributed to Unit E deposited between c.25 and 14 ka. Four artefacts are attributed to Unit F, deposited c.8 ka. Three artefacts from the Golgol lag are of unknown age. Usewear indicates a likely seed grinding function for 14 of the artefacts. Use‐related residues include starch, cellulose and collagen. The results of this study provide additional support for Pleistocene plant processing and seed grinding activities in Sahul.